Modelling knowledge-based systems using UML profiles - Abdullah, Mohd Syazwan; Benest, Ian; Evans, Andy; Kimble, Chris (2004)
Knowledge-based systems (KBS) play an important role in managing an organisation's knowledge initiated through knowledge management processes.These systems are designed, and developed using knowledge engineering techniques that are similar to software engineering, but have more emphasis on the rdles of knowledge in the reasoning process.However, there are no modelling techniques available in this field and most of the techniques that are used are usually adapted from the software engineering domain. The Unified Modeling Language (UML) is a general-purpose language that can he extended to model requirements from domains that are not currently defined by it.One such extension mechanism is the UML Profile which extends the language at the meta-level without changing the main construct of the language.This paper presents an initial profile that can be used to design a KBS.